Pengaruh Personality Traits Terhadap Tax Evasion Attitudes Dengan Pemoderasi Religiosity Dan Love Of Money - Suwartono; Umi Muawanah; Oyong Lisa (Program Studi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
This study aims to examine and analyze how personality traits influence tax evasion attitudes, moderated by religiosity and love of money. This research is a quantitative study using primary data sources. Data was collected through questionnaires distributed to participants. The research sample was selected using a purposive sampling technique. The data analysis method included descriptive statistical tests, classical assumption tests, multiple linear regression analysis, and moderation tests. The study's results indicate that personality traits positively influence tax evasion attitudes. Religiosity serves as a moderating variable of the predictor-moderator type, meaning it can affect the relationship between personality traits and tax evasion attitudes. However, it does not significantly moderate this relationship. Religiosity does not serve to strengthen or weaken the relationship between personality traits and tax evasion. Instead, it is more suitably classified as an independent variable. Love of money is a variable that moderates the relationship between personality traits and tax evasion attitude and also serves as an independent variable and a quasi-moderator. As a quasi-moderator, love of money strengthens the relationship between personality traits and tax evasion attitude.